The Integrative Role of Yoga on Chronic Pain Mechanisms and Mind-Body Connection - Mamta, Mamta Vijay; Kumari, Priyanka (International Research Journal of Ayurveda & Yoga, 2025)
Pain is a complex experience involving perception, emotion, and cognition. Traditional therapies frequently overlook the interrelated mind-body processes necessary for efficient pain control. With an emphasis on neuroplasticity, stress response, autonomic control, and pain perception, this descriptive study explores the integrative effects of yoga on pain mechanisms and the mind-body link. This study reviews research on yoga therapies, including asanas (postures), Pranayama (breath regulation), and meditation. The primary database sources (PubMed, Embase, Scopus, and Google Scholar) were searched bibliographically. Analysis was done on mechanisms such as endorphin release, central pain pathway regulation, and neurophysiological balance restoration. The effects of yoga poses, pranayama, and meditation on endorphin release and central pain pathways were examined in a literature review. Research indicates that yoga enhances vagal tone, promotes neuroplasticity, reduces pain sensitization, and restores autonomic balance. It fosters awareness, lowers stress, and strengthens emotional resilience. To prove yoga’s place in all-encompassing pain management, more study is required.